Let [tex]S_n = \sum\limits_{k=0}^n x^k[/tex]. Then
[tex]S_n = 1 + x + x^2 + \cdots + x^n[/tex]
[tex]xS_n = x + x^2 + x^3 + \cdots + x^{n+1}[/tex]
[tex]\implies (1 - x) S_n = 1 - x^{n+1}[/tex]
[tex]\implies S_n = \dfrac{1 - x^{n+1}}{1 - x}[/tex]
[tex]\implies \displaystyle \sum_{k=0}^{2019} x^k = S_{2019} = \frac{1 - x^{2020}}{1 - x}[/tex]
Let [tex]S_n' = \sum\limits_{k=1}^n k x^k[/tex]. (Starting the sum at k = 0 doesn't change its value.) Then
[tex]\displaystyle S_n' = \sum_{k=1}^n k x^k[/tex]
[tex]\displaystyle S_n' = x \sum_{k=1}^n k x^{k-1}[/tex]
[tex]\displaystyle S_n' = x \sum_{k=0}^{n-1} (k+1) x^k[/tex]
[tex]\displaystyle S_n' = x \left(\sum_{k=0}^{n-1} kx^k + \sum_{k=0}^{n-1} x^k\right)[/tex]
[tex]\displaystyle S_n' = x (S_{n-1}' + S_{n-1})[/tex]
[tex]\displaystyle S_n' = x (S_n' - nx^n) + xS_{n-1}[/tex]
[tex]\implies S_n' = \dfrac{x - (n+1)x^{n+1} + nx^{n+2}}{(1-x)^2}[/tex]
[tex]\implies \displaystyle \sum_{k=1}^{2018} kx^k = S_{2018}' = \dfrac{x - 2019x^{2019} + 2018x^{2020}}{(1-x)^2}[/tex]
So, the integrand reduces considerably to
[tex]\dfrac1{x-1} + \dfrac{S_{2018}' + S_{2018}}{S_{2019}} = \dfrac{2020 x^{2019}}{x^{2020}-1}[/tex]
and its integral is trivial; by substitution,
[tex]\displaystyle \int \frac{2020x^{2019}}{x^{2020}-1} \, dx = \int \frac{d(x^{2020}-1)}{x^{2020}-1} = \boxed{\ln\left|x^{2020}-1\right| + C}[/tex]